The continuity of learning in a translanguaging science classroom - Karlsson, Annika; Nygård Larsson, Pia; Jakobsson, Anders (Cultural studies of science education, 2020)
This article aims to explore and clarify how students’ use of first and second languages in a translanguaging science classroom (TSC) may affect the continuity of learning in science. In a TSC, participants can use all available language resources, in all meaning-making situations. An ethnographic data collection and research design is used to capture the authentic language use in this practice. The study followed monthly science lessons at a primary school for 3 years (2012–2015) and was documented by four video cameras and four audio recorders. The data material also consists of recorded conversations with four students, newly arrived in Sweden at the time of the data collection. In addition, field notes, students’ texts and different teaching materials were collected. To analyze how the use of both first and second languages may affect the continuity of science learning in multilingual classroom activities, practical epistemology analysis is used. The analysis shows that a TSC is an asset in appropriating a new social practice for students with limited ability to understand and express themselves in the language of instruction. However, the analysis also reveals some situations within this practice, in which all available resources are not utilized. These situations seem to be consequences of low expectations of students with limited access to the language of instruction expressed in simplified language usage; contextualizing the subject matter to everyday experiences students may not share; and the complexity of translating and transforming scientific content from one national language into another (Arabic and Swedish) and between everyday and academic discourse. The study contributes to the field by illustrating the importance of supporting each student’s access to the language tools that constitutes the scientific subject matter, as well as promoting the use of all resources to relate this to prior experience for a continuity of learning in a multilingual science classroom.